2019
DOI: 10.1111/jora.12446
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Effortful Control as Predictors of Indonesian Adolescents’ Tobacco and Alcohol Use: Moderation and Mediation

Abstract: Moderation and mediation models of religiosity and effortful control as predictors of tobacco and alcohol use were tested in this 2‐year longitudinal study of 563 16‐year‐old Muslim Indonesian adolescents. Adolescents reported their effortful control, religiosity, and tobacco and alcohol use and peers provided reports of adolescents’ effortful control. Although both moderation and mediation effects emerged when predicting Year 2 substance use, predictions of change from Year 1 to Year 2 substance use yielded e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…EC is closely tied to executive functioning (EF) (Zhou, Chen, & Main, 2012) and influenced by genes and the environment over time (Posner & Rothbart, 1998). Indeed, there is evidence that a variety of environmental factors impact developmental trajectories of EC throughout adolescence and emerging adulthood (Eisenberg et al, 2005; Fosco, Caruthers, & Dishion, 2012). Brain-imaging studies suggest that EC is linked to changes in critical regions in the prefrontal cortex that underlie executive functions and that remain plastic throughout adolescence and emerging adulthood (Selemon, 2013; Vijayakumar et al, 2014; Wei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…EC is closely tied to executive functioning (EF) (Zhou, Chen, & Main, 2012) and influenced by genes and the environment over time (Posner & Rothbart, 1998). Indeed, there is evidence that a variety of environmental factors impact developmental trajectories of EC throughout adolescence and emerging adulthood (Eisenberg et al, 2005; Fosco, Caruthers, & Dishion, 2012). Brain-imaging studies suggest that EC is linked to changes in critical regions in the prefrontal cortex that underlie executive functions and that remain plastic throughout adolescence and emerging adulthood (Selemon, 2013; Vijayakumar et al, 2014; Wei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The correlations between the three subscales ranged between 0.48 and 0.72. This scale had good internal consistency and longitudinal stability in prior Indonesian studies (e.g., French et al, 2014;French, Purwono, Zhao, Shen, & Eisenberg, 2019).…”
Section: Methodsmentioning
confidence: 89%
“…In several studies of Indonesian adolescents, religiosity was negatively associated with antisocial behavior (i.e., tobacco or alcohol use, a problem behavior composite score that incorporated substance use and minor rule breaking and delinquent activities, or aggression toward peers). In a 2-year longitudinal study of 16year-old adolescents, French et al (2019) found that religiosity negatively predicted both tobacco and alcohol use. In studies using a different sample than the one just reported, French, Eisenberg, Vaughan, Purwono, and Suryanti (2008) and Sallquist, Eisenberg, French, Purwono, and Suryanti (2010) found that self-rated and parent-rated adolescent religiosity were negatively associated with adolescent-rated problem behavior (i.e., lying, stealing, tobacco and alcohol use, and rule breaking) both concurrently and longitudinally.…”
Section: Religiosity: Associations With Externalizing and Internalizi...mentioning
confidence: 99%
“…There are a variety of ways that religiosity may contribute to the causal trajectory of antisocial behavior. First, adolescents who have a tendency to break rules and exhibit low self-regulation are likely to disobey both religious rules (i.e., religiosity) and societal rules (i.e., antisocial behavior; French, Purwono, Zhao, Shen, & Eisenberg, 2019). Second, Indonesian Muslim adolescent religiosity is positively associated with parent religiosity (French et al, 2013), and parents who are low in religiosity may be more tolerant This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Religiosity: Associations With Externalizing and Internalizi...mentioning
confidence: 99%
See 1 more Smart Citation